Prospects and Challenges of Sustainable Economic Development in East Nusa Tenggara: Between Natural Resource Exploitation and Emerging Opportunities (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
East Nusa Tenggara (ENT) possesses substantial natural resource potential across the agricultural, fisheries, renewable energy, and tourism sectors. However, their utilization remains largely unsustainable and continues to face challenges such as excessive resource exploitation, environmental degradation, limited infrastructure, and low human resource quality. This study aims to analyze the prospects and challenges of sustainable economic development in ENT by highlighting natural resource management and opportunities for developing new economic sectors based on innovation and local wisdom. The findings indicate that ENT has strategic opportunities in renewable energy development, sustainable tourism, and agricultural diversification, although these are constrained by weak governance, socio-economic inequality, and vulnerability to climate change. Therefore, the economic transformation of ENT requires strengthened regulations, multi-stakeholder collaboration, and sustainability-oriented investment. The findings underscore the necessity of fostering a sustainable economic transformation in ENT that aligns with global environmental goals while respecting local traditions and resources. This research provides valuable insights for policymakers, businesses, and community stakeholders aiming to promote sustainable growth in the region.